Domain-Based Functional Improvements in Bipolar Disorder After Interpersonal and Social Rhythm Therapy - Moot, William; Crowe, Marie; Inder, Maree; Eggleston, Kate; Frampton, Christopher; Porter, Richard J. (Frontiers in Psychiatry, 2022)
Background: Studies typically report overall change in function when assessing bipolar disorder (BD) interventions, but individual domains are not analysed. Which aspects of functioning are impacted is clearly important and may differ between treatments. Methods: Data were analysed from two previous clinical trials of Interpersonal and Social Rhythm Therapy (IPSRT) for BD patients. Change in total and subscale scores on the Social Adjustment Scale Self-Report (SAS-SR) from 0 to 78 weeks, were analysed. Results: 152 BD patients took part in randomised controlled trials of IPSRT (n=38) vs Specialist Supportive Care (SSC) (n=43), and of IPSRT (n=41) vs treatment as usual (TAU) which was discharge to primary care (n=30). IPSRT was superior to TAU on change in the social and leisure activities and extended family subscales, and SAS-SR total score over 18 months. Limitations: Studies were not designed to be pooled. Patients in study 1 were younger and symptomatic at baseline. Patients assigned to TAU were more likely to drop-out. Patients did not respond to subscales that were not personally applicable (work, marital, children). Conclusion: IPSRT had a positive impact on two SAS-SR subscales compared to TAU over 18 months. Other subscales were limited by the lack of respondents due to individual applicability. Different psychotherapy may have differential effects on different domains of function. Measures of function and research into functioning in BD should include domain-based measures, and report the numbers of participants who respond to questions in each domain.